Dosimetric impact of mechanical movements of the Linac gantry during treatments with small fields - McCallum-Hee, Broderick Ivan; Milan, Thomas; White, Rohen; Rowshanfarzad, Pejman (Frontiers in Oncology, 2022)
Objective: Current accepted linac Quality Assurance (QA) guidelines used for Volumetric Modulated Arc Therapy (VMAT) suggest a mechanical isocentre tolerance level of 1 mm. However, this tolerance level has not been well-established for the specific case of small field stereotactic VMAT. This study aims to evaluate the clinical impact of mechanical uncertainty on this treatment modality by modelling systematic gantry sag derived isocentre variance in the Treatment Planning System (TPS). Approach: A previously reported dataset of gantry sag values in the literature served as a starting point for this study. Using an in-house developed VMAT arc splitting algorithm, isocentre shifts were applied at a Control Point (CP) level to DICOM-RT treatment plans. Dose distributions for varying isocentre shift magnitudes were calculated for a set of 29 stereotactic VMAT plans using the Eclipse Acuros XB dose algorithm. These plans had a range of Planning Target Volume (PTV) sizes. A quantitative comparison of each plan was conducted by evaluating five Dose Volume Histogram (DVH)-derived plan quality metrics. Results: All metrics exhibited a deterioration in plan quality with increasing magnitudes of isocentre shift. At small PTV sizes, these effects were amplified, exhibiting significant changes at 1 mm of average shift when typical targets and tolerances were considered. For plans with PTVs between 0 and 5 cm3, a 1 mm shift reduced PTV coverage by 6.6 ± 2.2% and caused a 12.1 ± 3.8% deterioration in the conformity index. Based on the results of this study, the prevalent tolerance of 1 mm may not be suitable for treatments of small PTVs with small fields. Significance: In contrast to commonly accepted values, an absolute mechanical isocentre of 0.5 mm with action level at 0.75 mm is recommended for stereotactic VMAT of PTV sizes below 10 cm3.